Exploring Lecturers’ Standpoints in Composing Digital Fiction and Students’ Multimodal Literacy Level - Fiftinova Fiftinova; Nandang Heryana; Ida Rosmalina (UIN Salatiga, 2022)
Multimodality which encourages the combination of text, image, sound, and videos could be varied from class to class. Multimodal literacy as a new dimension of literacy in the 21st century has emerged as a critical skill that EFL students must develop, given its role as a source of meaning in communication. The purpose of this study was to identify the level of students’ multimodal literacy and to identify lecturers’ standpoints on students’ multimodal literacy. This study was conducted both quantitatively and qualitatively and involved 71 EFL students who took creative writing subject in an English education program in one state university in South Sumatera. The data were collected by distributing a questionnaire from Bulut et al. (2015) and by interviewing 3 lecturers who taught the subject. Descriptive statistics and one-way ANOVA were used to determine mean, standard deviation and differences in terms of gender and classes with different lecturer; qualitative data were thematically analyzed to categorize the themes. The results indicated that students’ multimodal literacy level was categorized high as indicated by the mean of each aspect of questionnaire: 4.22, 4.11 and 3.6 respectively. There was no different level of multimodal literacy between male and female students, and different lecturers with different instructions did not influence the level.. Finally, the lecturers perceived positively to students’ multimodal literacy . Similarly, referring to the lecturers’ view, the students gave positive attitude towards multimodal writing and hence making their multimodal digital fiction successful. Keywords: Multimodal Literacy, Digital Fiction, Creative Writing, EFL